pET28g: A Golden Gate-compatible pET vector for protein expression in Escherichia coli, validated by production of functional human ACE2 - Inês M. Luís; Mariana Parada; João B. Vicente; Isabel A. Abreu (PLoS ONE, 2025)
The pET28g plasmid is a new tool for protein expression in Escherichia coli. It was derived from pET28a by replacing the traditional multiple cloning site with a Golden Gate cassette containing the lacZα reporter gene. The assembly of pET28g is based on Golden Gate cloning, and it was designed as an extension of the MoClo Toolkit (Addgene Kit #1000000044). The pET28g plasmid, along with the level 0 modules developed in this work, expands the existing pET plasmid collection and offers a versatile and modular system for protein expression. These tools facilitate the establishment of efficient pipelines for the preparation and testing of multiple constructs, enabling the optimization of conditions to achieve high levels of soluble protein expression. As proof of concept, we successfully produced and purified the peptidase domain of human ACE2 using the pET28g system. Notably, this represents the first report of the successful purification of a functional human ACE2 protein from the Escherichia coli soluble protein fraction. This lab protocol, which is complemented by the protocol at www.protocols.io (https://www.protocols.io/view/preparation-of-level-0-modules-for-golden-gate-ass-j8nlk9e75v5r/v1), provides a comprehensive guide to understanding the nomenclature of the pET28g system and includes step-by-step instructions for the preparation of level 0 modules and the assembly of the final plasmid to express constructs of interest using pET28g.